Surface Plasmon-Induced Band Gap in the Photocurrent Response of Organic Solar Cells - Ribal Georges Sabat; Marcos Jose Leite Santos; Paul Rochon (International Journal of Photoenergy)
A 260 nm layer of organic bulk heterojunction blend of the polymer poly(3-hexylthiophene) (P3HT) and the fullerene [6,6]-phenyl C61-butyric (PCBM) was spin-coated in between aluminum and gold electrodes, respectively, on top of a laser inscribed azo polymer surface-relief diffraction grating. Angle-dependent surface plasmons (SPs) with a large band gap were observed in the normalized photocurrent by the P3HT-PCBM layer as a function of wavelength. The SP-induced photocurrents were also investigated as a function of the grating depth and spacing.